EVALUATION OF FETAL GROWTH IN BIOMETRICS ULTRASOUND TWINS AND SMALL SUITABLE FOR AGE GESTATIONAL - Acosta, Elard (2015)
OBJECTIVE. To determine fetal growth of appropriate and small for gestational age twins by ultrasound. MATERIAL AND METHODS. Live twin deliveries attended at A. Loayza General Hospital between January 1, 1996 and December 31, 2000, with minimum 3 ultrasound studies during pregnancy when biparietal diameter, abdominal circumference, femur length and estimated fetal weight were determined. Seventy-nine adequate (AGA) and small (SGA) for gestational age were studied, mcluding sexgender, placenta type and complications. RESULT. The abdominal circumference between twin AGA and SGA reaches a difference of 20 mm at 39,2 weeks, 15 mm at 35,6, and 10 mm at 31,1 weeks. Biparietal diameter differed 5 mm at 39,6 weeks, 4 mm at 30,4 and 3 mm at 25,2 weeks, Femur length reached maximum difference of 2,81 mm at 17,4 weeks and fetal weight 17% at 28,8 weeks. No significant differences were found with regards to sex and placenta type; fetal growth retardation was more significant in SGA. CONCLUSIONS. Adequate for gestational age twins growth pattern differ from that of small for gestational age, with clinically significant late differences in both abdominal circumference and biparietal diameter. At the 2nd trimester differences become evident in both BPD and fetal weight.